Politik Hukum yang Terdapat pada Pertimbangan Hakim dalam Perkara Pidana di Indonesia - Ismaidar Ismaidar; Tamaulina Br. Sembiring; Jesslyn Elisandra Harefa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Political law is the basic policy that is the basis for the formation, implementation and enforcement of law in a country. In the context of criminal cases in Indonesia, legal politics is reflected in the judge's considerations when handing down a decision. This research aims to analyze how legal politics influences judges' considerations in criminal cases and the extent to which these factors reflect substantive justice, legal certainty and legal benefits. By using a normative juridical approach and analysis of court decisions, this research finds that judges' considerations are influenced by various factors, such as statutory regulations, legal doctrine, jurisprudence, and social values ​​that develop in society. The legal politics applied by judges in their decisions often show an attempt to balance the need for legal certainty with substantive justice. However, in some cases, it was found that judges' considerations could be influenced by external pressures or developing political dynamics, which had the potential to cloud the principle of judicial independence. These findings provide important insights for policy makers and law enforcers to strengthen a justice system that is oriented towards justice and integrity.